The Clinical Characteristics and Prediction Nomograms for Primary Spine Malignancies - Zhou, Lei; Huang, Runzhi; Wei, Ziheng; Meng, Tong; Yin, Huabin (Frontiers in Oncology, 2021)
Background: Primary spine malignancies (PSMs) are relatively rare in bone tumors. Due to their rarity, the clinical characteristics and prognostic factors are still ambiguous. In this study, we aim to identify the clinical features and proposed prediction nomograms for patients with PSMs. Methods: Patients diagnosed with PSMs including chordoma, osteosarcoma, chondrosarcoma, Ewing sarcoma and malignant giant cell tumor of bone (GCTB) between 1975 and 2016 were selected from the Surveillance, Epidemiology, and End Results (SEER) database. The patient and tumor characteristics were described based on clinical information. The significant prognostic factors of overall survival (OS) and cancer-specific survival (CSS) were identified by the univariate and multivariate Cox analysis. Then, the nomogram for OS and CSS were established based on the selected predictors and their accuracy was explored by the Cox-snell residual plot, area under the curve (AUC) of receiver operator characteristic (ROC) and calibration curve. Results: The clinical information of 1,096 patients with PSMs were selected from the SEER database between 1975 and 2016. A total of 395 patients were identified with full survival and treatment data between 2004 and 2016. Chordoma is the commonest tumor with 400 cases, along 172 cases with osteosarcoma, 240 cases with chondrosarcoma, 262 cases with Ewing sarcoma and 22 cases with malignant GCTB. The univariate and multivariate analysis revealed that older age (Age > 60), distant metastasis, chemotherapy and Surgery were independent predictors for OS and/or CSS. Based on these results, the nomograms were established with a better applicability (AUC for CSS: 0.784; AUC for OS: 0.780). Conclusions: This study provides the statistics evidence for the clinical characteristics and predictors for patients with PSMs based on a large size population. Additionally, precise prediction nomograms were also established with a well-applicability.